2014
DOI: 10.1049/el.2014.0237
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of LTE signals as illuminators of opportunity for passive bistatic radar applications

Abstract: Passive radars utilising illuminators of opportunity are being actively studied in the field of radar. In the last few years, many illuminator sources have been employed for passive radar applications. However, there have been no published results on the use of the long‐term evolution (LTE) signal as a novel source for passive radar applications. For the first time an experimental investigation into the feasibility of LTE‐based passive radars for detecting a moving target is presented. A theoretical analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…PBR offers many advantages over conventional monostatic radar systems, including lower cost, harder to detect, higher immunity to electronic countermeasures, no requirement for frequency allocation, and the ability to counter stealth targets due to the bistatic configuration of PBR systems. Therefore, many kinds of civil illuminators have been exploited by PBR systems, such as FM radio [1], Integrated Services Digital Broadcasting-Terrestrial (ISDB-T) [2], Digital Video Broadcasting-Terrestrial (DVB-T) [3][4][5], Long-Term Evolution (LTE) [6], Wireless Fidelity (Wi-Fi) [7], and Global Navigation Satellite System (GNSS) [8]. However, those communications signals are not designed for use in radar, which may cause ambiguities due to the signal structure [9], and the maximum detectable range may be small due to the limited transmitting power.…”
Section: Introductionmentioning
confidence: 99%
“…PBR offers many advantages over conventional monostatic radar systems, including lower cost, harder to detect, higher immunity to electronic countermeasures, no requirement for frequency allocation, and the ability to counter stealth targets due to the bistatic configuration of PBR systems. Therefore, many kinds of civil illuminators have been exploited by PBR systems, such as FM radio [1], Integrated Services Digital Broadcasting-Terrestrial (ISDB-T) [2], Digital Video Broadcasting-Terrestrial (DVB-T) [3][4][5], Long-Term Evolution (LTE) [6], Wireless Fidelity (Wi-Fi) [7], and Global Navigation Satellite System (GNSS) [8]. However, those communications signals are not designed for use in radar, which may cause ambiguities due to the signal structure [9], and the maximum detectable range may be small due to the limited transmitting power.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, passive bistatic radar (PBR) has become an emerging technology owing to its covert detection and lower cost compared to active radar systems. Therefore, many kinds of illuminators are exploited as transmitter, such as FM radio [1][2][3], television [4], satellites [5,6], cellular phone downlink [7,8], WIFI [9,10], digital video broadcasting, and digital audio broadcasting [11][12][13]. However, these researches mainly focus on civil illuminators.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the LTE signal is attractive to be used for passive radar applications since it can achieve a good range and Doppler resolution of 8.6 m and 0.132 m/s, respectively. These preliminary results motivated us to continue to conduct an experimental investigation into the feasibility of LTE waveform for passive radar [13], where analytical analysis was conducted on a captured LTE signal in the atmosphere (received from real LTE eNB). Despite the positive results shown, there is still the need for experimental studies to investigate LTE-based passive radars' capability of detecting moving targets.…”
Section: Introductionmentioning
confidence: 99%